The lunchbox movement : better your life, one lunch at a time - Chong, Hui Qi (2017)
This paper presents "The Lunchbox Movement: Better your life, one lunch at a time", a campaign initiated by four final year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. The campaign aimed to promote healthy eating habits through the consumption of home-packed lunches at least twice a week, among university students.